OBSESSIVE COMPULSIVE DISORDER AS PREDICTOR OF POST BASIC SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN MATHEMATICS IN ADAMAWA STATE, NIGERIA - OWONWAMI, I. T; FARANSA, BABALE DANAN; SAMUEL, MIDENDA JUNIOR; NJIDDA, FADIMATU MUHAMMAD (Sokoto Educational Review, 2025)
Academic Achievement in Mathematics in Adamawa State, Nigeria. One research question and one hypothesis were formulated for the study. Correlation research design was adopted. Population of the study comprised of 3,314 SS II Mathematics students using 10% paradigm. Multi-stage sampling was used to select 336 students which is the 10% of the total population. Mathematics Students’ Obsessive Compulsive Disorder Questionnaire (MSOCDQ) and a student’s pro-forma result were used for data collection. The MSOCDQ was validated Cronbach’s alpha method was used to determine the reliability of the instrument and a reliability of 0.81 was obtained. Descriptive statistics of mean and standard deviation were used to answer the research question while, the hypothesis was tested at 0.05 level of significance using linear regression analysis. The findings of the study showed average score, which is 3.92, indicates that these students were highly when it comes to Obsessive Compulsive Disorder, hypothetically, Obsessive Compulsive Disorder predicts Post Basic schools students’ academic achievement in Mathematics (r = 0.79 R-square = 0.62, ? = -0.79; t = -25.23, p < 0.05). In conclusion Obsessive Compulsive Disorder is a serious and often debilitating mental health condition that can have negative impacts on various areas of an individual's life, including academic achievement in Mathematics in Adamawa State. Therefore, it was recommended that Test anxiety can be a significant challenge for individuals with panic disorder. Developing coping strategies, such as deep breathing or visualization techniques, can help reduce anxiety and improve performance on tests.